Conservative management of acute fissure in ANO and conversion into chronic fissure: A comparative study - Arvind Kumar Shukla; Avinash Gautam; Saranshi Shrivastava; Manish Kaushal; Nishant Kumar; Sahaj Dhakad (Asian Journal of Medical Sciences, 2023)
Background: The aim of the study was to choose best method for the management of acute fissure-in-ano, by comparing among zinc oxide cream and lidocaine ointment and conversion of acute fissure into chronic fissure-in-ano. Aims and Objectives: The aim of the study was to compare the effect of zinc oxide cream and lidocaine ointment in acute fissure and conversion of acute fissure into chronic fissure-in-ano requiring surgery. Materials and Methods: Two hundred patients who were diagnosed with acute anal fissure between November 2021 and November 2022 at MGM Medical College and M. Y. Hospital were undertaken for this prospective randomized trial. All cases randomized into two groups. Group 1 where the patients of acute anal fissure who applied 15% of zinc oxide cream twice a day. Group 2 where the patients would apply 5% of lidocaine ointment twice a day. Healing rates, pain relief, recurrences, changes in symptoms after the treatment, and complications were recorded. Results: There was no statistical difference among groups in terms of age and gender. The healing and symptomatic relief with the conservative method for acute anal fissure was significantly much more. Recurrence rate was very less in symptomatic group. There was a significant reduction in conversion of acute anal fissure into chronic anal fissure with the use of conservative management. Conclusion: Conservative management is better treatment option for acute fissure-in-ano with reduced conversion into chronic fissure-in-ano.